Risk factors for adverse fetal outcomes among women with early‐ versus late‐onset intrahepatic cholestasis of pregnancy. Issue 3 (8th November 2014) - Jin, Jin; Pan, Shi‐lei; Huang, Li‐ping; Yu, Yan‐hong; Zhong, Mei; Zhang, Guo‐wei
Abstract: Objective: To determine risk factors for adverse fetal outcomes (AFOs) among women with intrahepatic cholestasis of pregnancy (ICP) on the basis of time of onset. Methods: In a retrospective analysis, data were obtained for all women with ICP admitted to two centers in Guangzhou, China, between February 1, 1993, and January 31, 2014. Patients were divided into group A (early‐onset ICP) and group B (late‐onset ICP), and were further divided on the basis of severity. The frequency of AFOs was assessed. Results: Among 371 eligible women, 57 (15.4%) were in group A and 314 (84.6%) in group B. AFOs affected 20 (35.1%) women in group A and 67 (21.3%) in group B ( P = 0.024), and 12 (54.5%) of 22 women in group A and 21 (29.6%) of 71 in group B with severe ICP ( P = 0.032). Independent risk factors for AFO in group A were increased levels of serum bile acid ( P = 0.016) and alkaline phosphatase ( P = 0.004). Independent risk factors in group B were increased levels of alkaline phosphatase ( P < 0.001) and gamma‐glutamyl transpeptidase ( P = 0.001). Conclusion: Early‐onset ICP is associated with a higher frequency of AFO than is late‐onset ICP, especially in severe disease. The risk factors differ between early‐onset and late‐onset ICP.